Analysis of Stenting versus Non-Stenting in patients Undergoing Ureteroscopic Lithotripsy for Management of Ureteric Calculi - Aziz Ul Wahab, Numan Alam, Adee Hussain, Izhar Ali, Ijaz Khan, Zahoor Iqbal Mirza (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Ureteroscopic lithotripsy (URL) for ureteric calculi is commonly followed by ureteric stenting in around 60% of patients. However, its use for ureteric stones is debatable due to the stent-related symptoms and extra risks of stent migration, stent encrustation, and vesicoureteral reflux. Aim: To compare stenting to no-stenting in terms of mean operative time and mean hospital stay in patients receiving ureteroscopic lithotripsy for the treatment of ureteric calculi. Methods: This RCT, conducted at the Armed forces institute of urology Rawalpindi, included 104 patients aged 18 to 65 years with newly diagnosed ureteric calculi of 10-20 mm in size. They were subsequently separated into two equal groups, group A patient underwent ureteric stenting, and group B patients without a ureteric stent after uncomplicated calculus clearance with URL. Operative time was recorded in minutes, and hospital stay was measured in hours. Data were analyzed by SPSS version 22. Results: The mean (SD) operative time was significantly longer in group A as compared to Group B, 48.02 ± 4.33 and 33.67 ± 2.27 min, respectively (p-value <0.0001), similarly mean duration of hospital stay for Group B patients was significantly shorter as compared to Group A patients (21.94 ± 2.29 versus 27.10 ± 4.16 hours) which were significant statistically (p < 0.0001). Practical implication: Every URS procedure does not need stenting. Patients with uncomplicated URS should not under DJ stenting. URS without stenting reduces hospital stay and operative time. Conclusions: Non-stenting has reduced mean hospital stay duration and reduced mean operative time in comparison with stenting after URL; thus, unless desirably needed stenting in URL should be avoided. Keywords: Ureteroscopy (URL), DJ stenting, operative time. hospital stay. Keywords: Ureteroscopy (URL), DJ/JJ stenting, operative time.Hospitalstay.